Conductive Metal–Organic Frameworks with Extra Metallic Sites as an Efficient Electrocatalyst for the Hydrogen Evolution Reaction. Issue 9 (16th March 2020) - Huang, Hao; Zhao, Yue; Bai, Yimin; Li, Fumin; Zhang, Ying; Chen, Yu
Abstract: The 2D conductive metal–organic frameworks (MOFs) are expected to be an ideal electrocatalyst due to their high utilization of metal atoms. Exploring a new conjugated ligand with extra active metallic center can further boost the structural advantages of conductive MOFs. In this work, hexaiminohexaazatrinaphthalene (HAHATN) is employed as a conjugated ligand to construct bimetallic sited conductive MOFs (M23 (M13 ∙HAHATN)2 ) with an extra M–N2 moiety. Density functional theory (DFT) calculations demonstrate that the 2D conjugated framework renders M23 (M13 ∙HAHATN)2 a high electric conductivity with narrow bandgap (0.19 eV) for electron transfer and a favorable in‐plane porous structure (2.7 nm) for mass transfer. Moreover, the metal atom at the extra M–N2 moiety has a higher unsaturation degree than that at M–N4 linkage, resulting in a stronger ability to donate electrons for enhancing electroactivity. These characteristics endow the new conductive MOFs with an enhanced electroactivity for hydrogen evolution reaction (HER) electrocatalysis. Among the series of M23 (M13 ∙HAHATN)2 MOF, Ni3 (Ni3 ∙HAHATN)2 nanosheets with the optimal structure exhibit a small overpotential of 115 mV at 10 mA cm −2, low Tafel slope of (45.6 mV dec −1 ), and promising electrocatalytic stability for HER. This work provides an effective strategy for designing conductive MOFs with a favorable structure for electrocatalysis. Abstract : Hexaiminohexaazatrinaphthalene (HAHATN) is employed as a conjugated ligand to introduce an extra M–N2 moiety for constructing M23 (M13 ∙HAHATN)2 conductive metal–organic frameworks (MOFs) (M1 = Ni or Co or Cu; M2 = Ni or Cu). The extra metal atom in the M1–N2 moiety exhibits a higher unsaturated degree than that in traditional M2–N4 linkage, which remarkably enhances the electroactivity of conductive MOFs.